Implementasi Sistem Aquaponik sebagai Media Pembelajaran pada Modul P5PPRA di Madrasah Aliyah Hidayatul Insan - Jamalika Bunga Nur Siammukaromah; Noor Hujjatusnaini (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
Education through the Merdeka curriculum, particularly the Pancasila Student Profile Strengthening Project Module (P5), focuses on the development of students' character and skills. The implementation of the aquaponics system in madrasahs is expected to enhance students' scientific understanding, critical thinking skills, and environmental awareness. This community service method includes the planning, implementation, and evaluation of the aquaponics system at the school to support P5PPRA. The research findings indicate that the application of the aquaponics system at the school successfully improved students' understanding of ecosystems, as well as technical skills and teamwork in system maintenance. In conclusion, the aquaponics system is effective as a learning medium that supports the implementation of the P5PPRA module.